2016
DOI: 10.1186/s12889-016-3810-6
|View full text |Cite
|
Sign up to set email alerts
|

Health literacy among different age groups in Germany: results of a cross-sectional survey

Abstract: BackgroundHealth literacy is of increasing importance in public health research. It is a necessary pre-condition for the involvement in decisions about health and health care and related to health outcomes. Knowledge about limited health literacy in different age groups is crucial to better target public health interventions for subgroups of the population. However, little is known about health literacy in Germany. The study therefore assesses the prevalence of limited health literacy and associated factors am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
154
2
14

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 180 publications
(186 citation statements)
references
References 23 publications
16
154
2
14
Order By: Relevance
“…Germany performed in the middle of the other seven participating European countries [124]. People of older age, people with low socioeconomic status, and high frequency of physician visits had lower health literacy scores [126,127]. Immigrants in general, but especially immigrants less than 65 years of age, had limited health literacy [125,126].…”
Section: Notable Health Literacy Implications For Fsu Immigrants In Gmentioning
confidence: 99%
“…Germany performed in the middle of the other seven participating European countries [124]. People of older age, people with low socioeconomic status, and high frequency of physician visits had lower health literacy scores [126,127]. Immigrants in general, but especially immigrants less than 65 years of age, had limited health literacy [125,126].…”
Section: Notable Health Literacy Implications For Fsu Immigrants In Gmentioning
confidence: 99%
“…It revealed that limited health literacy was associated with poor health status, having more than one long-term illness and the higher use of health care services involving six or more consultations with doctors in the last 12 months [4]. Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].Although the scope of information which arises from the HLS-EU-Q47 is extensive, it appears that the size of the tool may result in reduced compliance of respondents, especially if the questionnaire is used as a part of a survey which is also focused on other issues. Therefore, a shortened but also validated, the 16-item version has been used in many surveys (HLS-EU-Q16) [5,12,[25][26][27][28][29].…”
mentioning
confidence: 95%
“…It revealed that limited health literacy was associated with poor health status, having more than one long-term illness and the higher use of health care services involving six or more consultations with doctors in the last 12 months [4]. Other studies, in which national versions of the HL questionnaire developed within the HLS-EU project were used, confirmed that low HL may be associated with people's poor self-assessment of health status [12,20], the prevalence of long-term illnesses [12], the higher utilisation of health care resources [14,21], and a lower level of physical activity [22][23][24].…”
mentioning
confidence: 95%
“…The current study findings showed that there was a significant relationship between HL and age (P < 0.001), and that the older a participant was, the higher HL she had. The results of the studies by Jovic-Vranes et al 18 , Berens et al 19 and Peyman et al 16 showed that with increasing the age, health literacy decreased. This difference could be due to the limited age range of the present study (15 to 45 years).…”
Section: Discussionmentioning
confidence: 93%